Desenvolvimento de um protótipo de um atlas escolar interativo: Projecto e produção - De Oliveira Barros, Lígia Manccini [UNESP]; Decanini, Mônica Modesta Santos [UNESP] (My University, 2008)
This paper aims at presenting an Interactive School Atlas prototype which was developed for cartography and environmental education. The methodology was based on the theoretical study about child mental development of Piaget theory, in order to elaborate strategies that allow the student a better comprehension about the spatial information understanding. It was defined as study case of sixth grade students, because they belong to the Formal Operation stage, in which the children reach the needed mental operations for understanding cartographic key concepts. This Atlas was developed in two stages: cartographic design and Atlas production. The Atlas implementation was developed seeking the use of Multimedia Cartography and animation resources that may attract students and teachers, instigating them to explore the tools and strategies to lead users to a correct interpretation of map contents. The Atlas was implemented by using the Macromedia Flash and Visual Basic softwares and the MapObjects library. Though the map has bot been evaluated yet, one should point out that it was designed according to the theoretical and methodological knowledge of the cognitive development and its relationship to cartographic conceptions, aiming at adapting the product to children cognitive skills.
Development of an interactive scholar atlas prototype: Design and production
Keywords: Interactive animated map; Multimedia cartography; Scholar cartography